Efficacy and safety of pelvic floor magnetic stimulation combined with mirabegron in female patients with refractory overactive bladder: a prospective study - Liang, Ping; Tang, Qing-lai; Lin, Tao; Tang, Zheng-kun; Liu, Fa-de; Zhou, Xing-zhu; Tao, Rong-zhen (Frontiers in Neuroscience, 2024)
Objective To observe the efficacy and safety of pelvic floor magnetic stimulation (PFMS) combined with mirabegron in female patients with refractory overactive bladder (OAB) symptoms. Patients and methods A total of 160 female patients with refractory OAB symptoms were prospectively randomized into two groups. Eighty cases in the combination group accepted PFMS and mirabegron therapy and 80 cases as control only accepted mirabegron therapy (The clinical trial registry number: ChiCTR2200070171). The lower urinary tract symptoms, OAB questionnaire (OAB-q) health-related quality of life (HRQol), symptom bother score and OABSS between two groups were compared at the 1st, 2nd and 4th week ends. Results All of 160 patients were randomly assigned to two groups, of which 80 patients were included in the combination group and 80 in the mirabegron group. The incidences of LUTS, including urgency, frequent urination, and incontinence episodes, in the 2nd week and the 4th week after combination treatment were significantly lower than those in the mirabegron group (p < 0.05). The incidence of drug-related adverse events between two groups was similar, and there was no statistically significant difference (p > 0.05). With respect to secondary variables, the OAB-q HRQol score in the combination group was statistically superior in comparison with that in the mirabegron group between the 2nd week and the 4th week (p < 0.05). This was consistent with the primary outcome. Meanwhile, from the second to fourth week, the OAB-q symptom bother score and OABSS in the combination group were both lower than in the mirabegron group (p < 0.05). Conclusion Combination therapy of PFMS and mirabegron demonstrated significant improvements over mirabegron monotherapy in reducing refractory OAB symptoms for female patients, and providing a higher quality of life without increasing bothersome adverse effects. Clinical Trial Registration https://www.chictr.org.cn/, ChiCTR-INR-22013524.